COMPARISON OF RESORT SIGN SYSTEM BASED ON EFFECTIVENESS IN VISUAL COMMUNICATION DESIGN GOAL (Case Study: Kuta Beach Bali-Indonesia and Haeundae Beach Busan-Korea) - Natadjaja, Listia (Institute of Research and Community Outreach - Petra Christian University, 2005)
As we know there are many resorts in Indonesia especially in Bali. Each resort needs a sign system for information and safety. We need a field study from other countries to compare our sign system condition%2C so we can get some description of how to create an effective sign system and what we should do to make a better environment. This case study represents two famous beaches in two countries which are Kuta Beach in BaliÂ–Indonesia and Haeundae Beach in Busan-Korea. Through a study of another sign system%2C hopefully we can create an effective sign system that meets the Visual Communication Design Goal. Each area has a unique character%2C so a sign system can be developed by looking at the environment and local culture to reach a global understanding. Abstract in Bahasa Indonesia : Seperti yang kita ketahui ada begitu banyak tempat rekreasi di Indonesia utamanya di Bali. Tiap-tiap tempat rekreasi memerlukan sistem tanda untuk informasi dan keselamatan. Diperlukan suatu studi lapangan untuk membandingkan kondisi sistem tanda antar negara%2C sehingga didapatkan beberapa gambaran bagaimana menciptakan suatu sistem tanda yang efektif dan apa yang perlu dilakukan untuk membuat lingkungan yang lebih baik. Studi kasus yang diambil mewakili dua tempat rekreasi yaitu pantai yang terkenal di masing-masing negara yaitu pantai Kuta Bali-Indonesia dan pantai Haeundae di Busan-Korea. Dengan mempelajari sistem tanda yang berbeda%2C diharapkan dapat diciptakan suatu sistem tanda yang efektif untuk mencapai tujuan desain komunikasi visual. Tiap-tiap lokasi memiliki karakter yang unik%2C jadi sistem tanda dapat dikembangkan dengan melihat lingkungan dan budaya lokal untuk mencapai pengertian secara global. resort%2C sign system%2C effective%2C visual communication design goal.